Superconductivity of zirconium-nitrogen hydrides at megabar pressures - Tao Luo; Shen-Ao Li; Liu-Cheng Chen; Guo-Hua Zhong; Hai-Qing Lin; Xiao-Jia Chen (Communications Materials)
Abstract The hydrides based on transition metal nitrides are believed to be potential candidates of low-pressure superconductors. However, the relevant theoretical and experimental studies are lack. Here, we report a theoretical and experimental study of the superconductivity in Zr-N-H system. Two high-pressure phases of P63/m m c-ZrNH2 and $$F\bar{4}3m$$ F 4 ¯ 3 m -ZrNH are found to be stable. The superconducting transition temperature of the former is theoretically predicted to be relatively low with the values of 15–17 K, while the transition temperature of the latter is higher, close to 40 K at megabar pressures. The difference in transition temperature values mainly comes from the different forms of H in hydrides. To examine this theoretical prediction, we synthesize Zr-N-H ternary hydrides experimentally at high pressures by laser heating. The resistance measurements confirm the superconductivity of P63/m m c-ZrNH2 and $$F\bar{4}3m$$ F 4 ¯ 3 m -ZrNH. The present results provide a promising avenue for exploring the superconductivity in transition-metal nitrides.